Characterization of B- and T-Cell Compartment and B-Cell Related Factors Belonging to the TNF/TNFR Superfamily in Patients With Clinically Active Systemic Lupus Erythematosus: Baseline BAFF Serum Levels Are the Strongest Predictor of Response to Belimumab after Twelve Months of Therapy - Piantoni, Silvia; Regola, Francesca; Masneri, Stefania; Merletti, Michele; Lowin, Torsten; Airò, Paolo; Tincani, Angela; Franceschini, Franco; Andreoli, Laura; Pongratz, Georg (Frontiers in Pharmacology, 2021)
Background: Patients with systemic lupus erythematosus (SLE) show increased serum levels of tumor necrosis factor (TNF)/TNF receptor (R) superfamily member, e.g. BAFF (B lymphocyte stimulator). Belimumab, a monoclonal antibody against soluble BAFF, is used for treatment of SLE. Although B cells are the main target, a BAFF-dependent T-cell activation pathway also plays a role. High levels of anti-DNA antibodies and low complement at baseline are known predictors of response to Belimumab. Objectives: To explore the association of circulating lymphocytes and serum levels of B- cell related TNF/TNFR superfamily members with response to Belimumab in SLE patients. Methods: Twenty-one SLE patients received Belimumab. Clinical evaluation and laboratory tests were performed at baseline, at 6 and 12 months. TNF super-family members (BAFF, APRIL, sBCMA, sCD40L, sTACI, TWEAK) were tested by high-sensitivity ELISA in all patients, and lymphocyte immunophenotyping was performed by flow cytometry in ten subjects. SLE-disease activity was assessed by SLEDAI-2K score. Linear regression modeling was used to investigate parameters influencing SLEDAI-2K and anti-dsDNA antibody titers over time and for predictive models. Results: Clinical improvement was observed in all patients. A global reduction of circulating B cells, especially naïve, was detected, without variation in the T-cell compartment. All TNF family members decreased, whereas APRIL remained constant. The increase in serum levels of C3 (p = 0.0004) and sTACI (p = 0.0285) was associated with a decrease of SLEDAI-2K. The increase of C4 (p = 0.027) and sBCMA (p = 0.0015) and the increase of CD8+ T cells (p = 0.0160) were associated with a decrease, whereas an increase of sCD40L in serum (p = 0.0018) and increased number of CD4+ T cells (p = 0.0029) were associated with an increase, in anti-dsDNA antibody titers, respectively. Using stepwise forward inclusion, the minimal model to predict SLEDAI-2K response at 12 months included BAFF (p = 3.0e − 07) and SLEDAI-2K (p = 7.0e − 04) at baseline. Baseline APRIL levels also showed an association, although the overall model fit was weaker. Conclusion: In our real-life cohort, baseline serum levels of BAFF were the best predictor of response to Belimumab, confirming post-hoc results of the BLISS study and suggesting the utility of this particular biomarker for the identification of patients who are more likely to respond.